Quality characteristics of sous vide ready to eat seabream processed by high pressure. Issue 2 (December 2015) - Espinosa, Miriam C.; Díaz, Pedro; Linares, M. Belén; Teruel, M. Rocío; Garrido, M. Dolores
Abstract The effect of high pressure (HP) treatment at 300 and 600 MPa during 5 min at 5 °C, on the quality of sous vide ready to eat seabream (Sparus aurata) was investigated. Microbiological (total viable counts, Enterobacteriaceae, lactic acid bacteria, anaerobic psychrotrophic, mould and yeasts, Salmonella and Listeria monocytogenes), chemical and sensory analyses were made on days 0, 7, 17, 34, 48 and 62 of refrigerated storage (2 ± 1 °C). No significant differences (P > 0.05) in TVC values were found between unpressurized samples (C), HP300 and HP600 treatments and during the time of storage. High pressure treatment did not eliminate the total viable counts of sous vide ready to eat seabream. In all other microbial groups, counts were not detectable (<1 log cfu g−1) and pathogenic bacteria (Salmonella and L. monocytogenes) were absent. High pressure treatment did not have a pro-oxidant effect in the sous vide ready to eat seabream. In regards to the sensory quality, samples became were less firm as storage time increased, but not in treated samples. High pressure treatment at 600 MPa enhanced textural attributes and a high degree of sensory quality was reached in the sous vide ready to eat seabream product.